Analisis Framing Pemberitaan Danantara oleh Media Detik.com - Koswara, Iwan; Rantona, Safutra (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2025)
Mass media plays a strategic role in shaping public opinion through the construction of discourse known as framing. One of the recent cases illustrating this practice is the coverage of the Daya Anagata Nusantara Investment Management Agency (Danantara), a newly established sovereign wealth fund initiated by President Prabowo Subianto. This study aims to analyze how the framing of Danantara is constructed by the online news outlet Detik.com. The research employs Robert Entman’s framing model, which includes four elements: defining problems, diagnosing causes, making moral judgments, and suggesting remedies. Data were obtained from two Detik.com articles published on July 1 and 2, 2025. The findings reveal that Detik.com frames Danantara in a predominantly positive and symbolic manner, emphasizing diplomatic success and international trust while omitting critical or alternative viewpoints. The problem is defined as an achievement, the cause is attributed to elite leadership, the moral judgment supports policy legitimacy, and the remedy suggested is full public support. This study concludes that Detik.com's framing of Danantara reflects state interests more than the public's right to balanced and critical information.